2020
DOI: 10.3390/foods9060819
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly Nutritional Breads with By-Products of Chia (Salvia hispanica L.) Seeds

Abstract: The effect of the incorporation of various types of residual chia flour (whole, semi-defatted and defatted, with or without mucilage) on the technological quality of bread was investigated. The various types of chia flour were used to substitute 5 and 10% wt/wt of wheat flour in the bread formulations. The water absorption, dough development time and stability of blends with the presence of mucilage and the incorporation of 10% wt/wt of chia flour demonstrated the highest values in comparison with the other on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Each value represents the mean of three replicates ±SD. Mean values with the different letters in the same column mean significantly different at p≤0.05.Similar studies explained the nutritional value for wheat flour fortified with chia seeds(Hafeez et al, 2019 andGuiotto et al, 2020). Results are agreed with (Alamri, 2020) reported that protein content in each 100 g chia seed was around…”
supporting
confidence: 87%
“…Each value represents the mean of three replicates ±SD. Mean values with the different letters in the same column mean significantly different at p≤0.05.Similar studies explained the nutritional value for wheat flour fortified with chia seeds(Hafeez et al, 2019 andGuiotto et al, 2020). Results are agreed with (Alamri, 2020) reported that protein content in each 100 g chia seed was around…”
supporting
confidence: 87%
“…The color was determined as parameters related to the technological and functional quality of the seeds ( Guiotto et al, 2020 ). In this analysis, the color values indicated that there were significant differences when comparing cultivars or among year of sowing.…”
Section: Resultsmentioning
confidence: 99%
“…Color parameters were determined as described by Guiotto et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…According to Nazir et al, seed extraction with water at a temperature of 60 • C over 1.6 h provides a high yield of BSM, of about 20.5 g/100 g seed dry mass. The total dietary fiber content observed for basil seed mucilage was 98.5% [6,95].…”
Section: Ocimum Basiliummentioning
confidence: 95%
“…Chia mucilage-stabilized muffins composed of chia seeds, water, inulin, hemp, and flaxseed oil were analyzed by Gutierrez-Luna et al [83,94]. In another study, the technological quality of breads were improved when wheat flour was substituted with 5% and 10% (w/w) chia flour with mucilage [95]. It should be emphasized that the addition of chia flour and mucilage also improved the water absorption, dough development time, and the stability of the mixes during the preparation of bread.…”
Section: Application Of Plant-derived Mucilagementioning
confidence: 99%